2022
DOI: 10.1177/03635465221126506
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Horn Lateral Meniscal Oblique Radial Tear in Acute Anterior Cruciate Ligament Reconstruction Incidence and Outcomes After All-Inside Repair: Clinical and Second-Look Arthroscopic Evaluation

Abstract: Background: The term posterior horn lateral meniscal oblique radial tear (LMORT) has emerged to characterize the tear patterns of the lateral meniscus in many patients with acute anterior cruciate ligament (ACL) injury. There is a lack of data regarding the exact incidence according to the types of LMORT and clinical outcomes. Purposes: (1) To investigate the incidence of LMORT according to type in patients with acute ACL reconstruction (ACLR) and (2) to identify healing status after repair of LMORT via second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A recent series of 79 patients with minimum 2-year follow-up who underwent ACLR with LMORT repair reported a mean sIKDC score of 82.9. 11 A high activity level was maintained by patients in both groups in the current study, and the Tegner scores in our cohort were comparable with those of previously published series. Sonnery-Cottet et al 38 reported a mean Tegner score of 6.4 in patients undergoing iACLR.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A recent series of 79 patients with minimum 2-year follow-up who underwent ACLR with LMORT repair reported a mean sIKDC score of 82.9. 11 A high activity level was maintained by patients in both groups in the current study, and the Tegner scores in our cohort were comparable with those of previously published series. Sonnery-Cottet et al 38 reported a mean Tegner score of 6.4 in patients undergoing iACLR.…”
Section: Discussionsupporting
confidence: 90%
“…2,35,36 These findings suggest that ACL graft integrity could be compromised from a failure to repair the meniscus. 8 Regarding healing of these tears, second-look arthroscopy in LMORT tears as described by Jeon et al 11 showed 80.3% complete healing status and 19.7% partial healing status in 61 repaired LMORTs. As a substantial portion of the tear crosses obliquely through the red-red and red-white zones of the meniscus and repair is occurring during the time of ACLR, there is ample vascularity and stimulus to encourage healing of these tears when combined with anatomic repair.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations